EFFECTIVENESS OF MENIRAN (PHYLLANTHUS NIRURI LINN) AS ANTIBACTERIAL FOR RESISTANCE ANTIBIOTICS PREVENTION OF ENTEROTOXIN ESCHERICHIA COLI - Hidanah, Sri; Sabdoningrum, Emy Koestanti; Wahyuni, Retno Sri; Dewi, Arini Rahmi; Safitri, Erma - (Institute of Topical Disease Universitas Airlangga, 2018)
Escherichia coli (E. coli) can be isolated from the environment both inside and outside the hospes body. There were 89 serotypes in which showed 21% resistance to various antibiotics, such as enterotoxigenic E.coli. Alternative efforts are needed to overcome this, one of them through the use of medicinal plants, such as meniran (Phyllanthus niruri Linn). Meniran plant is an immunomodulator that serves to repair the immune system of the body. The aim of research is the research was done through several stages: isolation and identification of enterotoxigenic E. coli from several broiler farms in East Java using the polymerase chain reaction (PCR) method, E. coli resistance test against some antibiotics, making meniran extract and activation test against enterotoxigenic E. coli n The study was divided into five treatments: T0+ (group of chickens were infected by enterotoxigenic E. coli T0- (control group, not infected), T1 (infected by enteroxigenic E. coli + 20% meniran extract), T2 (infected by enterotoxigenic E. coli + 25% extract meniran), T3 (infected by enterotoxigenic E. coli + 30% extract meniran). Data were analyzed by ANOVA (Analysis of Variance). The results show that all of E. coli DNA isolates which tested by the PCR method show positive reactions at 600 bp. The next stage, the enterotoxigenic E. coli are resistant to some antibiotics, such as amoxicillin, ampicillin, erythromycin, cephalosporins, tetracycline, cloxacillin and gentamicin. Furthermore, the 30% Phyllanthus niruri Linn extract is effective as an antibacterial for antibiotic resistance enterotoxigenic E. coli. next necessary to write that: The 30% meniran extract is potential for kill of enterotoxigenic E. coli